2019
DOI: 10.2174/157488711404191016122006
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of Impaired Venous Outflow from the Brain in Neurodegeneration: Lessons Learned from the Research on Chronic Cerebrospinal Venous Insufficiency

Abstract: About 10 years ago, the so-called chronic cerebrospinal venous insufficiency syndrome was discovered. This clinical entity, which is associated with extracranial venous abnormalities that impair venous outflow from the brain, was initially found exclusively in multiple sclerosis patients. Currently, we know that such venous lesions can also be revealed in other neurological pathologies, including Alzheimer’s and Parkinson’s diseases. Although direct causative role of chronic cerebrospinal venous insufficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Recently, there has been increased importance in studying the pathology of veins and venules, not only in the context of AD or CAA, but also in small vessel disease and dementia overall [30,45,46]. Venous pathology has been shown to contribute to vascular dysfunction in AD, resulting in white matter hyperintensities and microinfarcts, and potentially induction of ischemia [30,[45][46][47][48]. However, more research is necessary to understand the role of veins and venules in AD and CAA.…”
Section: Evidence Of Aβ In Veins and Venulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been increased importance in studying the pathology of veins and venules, not only in the context of AD or CAA, but also in small vessel disease and dementia overall [30,45,46]. Venous pathology has been shown to contribute to vascular dysfunction in AD, resulting in white matter hyperintensities and microinfarcts, and potentially induction of ischemia [30,[45][46][47][48]. However, more research is necessary to understand the role of veins and venules in AD and CAA.…”
Section: Evidence Of Aβ In Veins and Venulesmentioning
confidence: 99%
“…been shown to contribute to vascular dysfunction in AD, resulting in white matter hyperintensities and microinfarcts, and potentially induction of ischemia [30,[45][46][47][48]. However, more research is necessary to understand the role of veins and venules in AD and CAA.…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Venous system dysfunction has been linked to a variety of brain disorders, including Alzheimer and Parkinson disease. 2 Several reports have indicated that IJV reflux and increased central venous pressure, typically measured by neck sonography, are associated with white matter changes in Alzheimer disease and in elderly individuals. 4,5,30 Chronic venous insufficiency in the dural venous sinuses and compromised jugular drainage also A, Among patients with spontaneous intracerebral hemorrhage (ICH) with cerebral amyloid angiopathy (CAA)-ICH or non-CAA ICH, patients with CVR have higher cerebral amyloid load.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral venous reflux is a manifestation of abnormal cerebral venous circulation due to systemic venous congestion, increased cerebral venous pressure, or age-related degeneration of venous valves. 1 Abnormal cerebral venous circulation may be associated with decreased cerebral perfusion, cerebral microvascular damage, impaired cerebral autoregulation, and altered cerebrospinal fluid dynamics 2,3 ; all of the features are closely related to central nervous system pathology.…”
mentioning
confidence: 99%
See 1 more Smart Citation